ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA SOAL CERITA PENJUMLAHAN DAN PENGURANGAN PECAHAN KELAS V - Maerlin, Maerlin Windtari; Nur Ngazizah; Rintis Rizkia Pangestika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Many students and teachers do not know the difficulties of learning Mathematics and its factors in the story of addition and subtraction of fractions. The purpose of the study is to find out the learning difficulties and the factors that cause learning difficulties in Mathematics for the story of addition and subtraction of class V fractions. The data source was selected using the purposive sampling technique. Data collection techniques use tests, questionnaires, interviews, and documentation. The analysis technique is based on the Miles and Huberman Model, namely data collection, data reduction, data presentation, and conclusion drawn. Data validity using triangulation techniques. The results of the research were difficulties in learning mathematics such as difficulties in concepts, applying principles, working on verbal problems, and reading. The influencing factors are internal factors and external factors. Internal factors consist of physiological factors such as poor physical health conditions of students and psychological factors, namely low intelligence levels, low concentration levels, poor attitudes and behaviors, lack of motivation, and lack of social interaction. Meanwhile, external factors consist of family factors, such as low parental education, lack of parental attention, and parental work. School factors, such as less varied teaching methods, not using learning media, and poor attitudes and behaviors of friends. Environmental factors around the place of residence, such as people who are indifferent to education, friends who are not peers, and jobs in the surrounding area.